Silver Nanoparticles and Their Antibacterial Applications - Bruna, Tamara; Maldonado-Bravo, Francisca; Jara, Paul; Caro, Nelson (International journal of molecular sciences, 2021)
Silver nanoparticles (AgNPs) have been imposed as an excellent antimicrobial agent being able to combat bacteria in vitro and in vivo causing infections. The antibacterial capacity of AgNPs covers Gram-negative and Gram-positive bacteria, including multidrug resistant strains. AgNPs exhibit multiple and simultaneous mechanisms of action and in combination with antibacterial agents as organic compounds or antibiotics it has shown synergistic effect against pathogens bacteria such as Escherichia coli and Staphylococcus aureus. The characteristics of silver nanoparticles make them suitable for their application in medical and healthcare products where they may treat infections or prevent them efficiently. With the urgent need for new efficient antibacterial agents, this review aims to establish factors affecting antibacterial and cytotoxic effects of silver nanoparticles, as well as to expose the advantages of using AgNPs as new antibacterial agents in combination with antibiotic, which will reduce the dosage needed and prevent secondary effects associated to both.